Predictive Efficacy Biomarkers of Programmed Cell Death 1/Programmed Cell Death 1 Ligand Blockade Therapy - Fang, Xiao-Na; Fu, Li-Wu (Recent Patents on Anti-Cancer Drug Discovery, 2016)
Inhibitors of immune check-point molecule, programmed cell death 1 (PD-1) and its ligand, programmed cell death ligand 1 (PD-L1) have attracted much attention in cancer immunotherapy recently due to their durable antitumor effects in various malignances, especially the advanced ones. Unfortunately, only a fraction of patients with advanced tumors could benefit from anti-PD-1/PD-L1 therapy, while others still worsened. The key to this point is that there are no efficient biomarkers for screening anti-PD-1/PD-L1-sensitive patients. In this review, we aim at summarizing the latest advances of anti-PD-1/PDL1 immunotherapy and the potential predictive efficacy biomarkers to provide evidences for identifying anti-PD-1/PDL1- sensitive patients. The present article also includes the patent review coverage on this topic.
Keywords: programmed cell death 1 ligand